Analysis of the therapeutic benefits of symptomatic slow acting drugs in osteoarthritis: emphasis on structural-modifying action - I. B. Belyaeva; V. I. Mazurov; E. A. Trofimov (Современная ревматология)
The review presents an analysis of the therapeutic effect in osteoarthritis (OA) of the original complex injectable drug Alflutop (bioactive concentrate of small marine fish), which is one of the most widely used symptomatic slow acting drugs (SYSADOA) in Russia. It stimulates the proliferation of chondrocytes, activates the synthesis of the extracellular matrix by modulating transforming growth factor β (TGFβ), inhibits hyaluronidase, oxidative stress and the activity of extracellular expression of proinflammatory cytokine genes – interleukin (IL) 1β, IL6 and IL8 in vitro.The results of prospective clinical studies are presented, which demonstrate the ability of Alflutop to slow down the X-ray progression of OA of the knee joints (inhibit the narrowing of the joint space, the growth of osteophytes and increase the intra-articular concentration of hyaluronic acid), as well as restore the mobility of the hip joints when it is locally introduced into the zone of pathological changes in the articular lip of the acetabulum. Combined therapy with Alflutop leads to activation of reparative processes and significant clinical improvement in patients with post-traumatic OA, and also slows down the progression of chondrodegeneration according to magnetic resonance imaging. The new Alflutop administration regimen for knee OA (2 ml every other day, №10) can increase patient adherence to therapy.The results of clinical studies presented in the review prove the structural-modifying effect of Alflutop in OA of various localization and substantiate its widespread use in this disease in rheumatological, traumatological and orthopedic practice.